MicroRNA-378a-3p regulates the progression of hepatocellular carcinoma by regulating PD-L1 and STAT3. Issue 3 (1st March 2022) - Li, Yaqin; Zhou, Tao; Cheng, Xianyi; Li, Dezhi; Zhao, Meng; Zheng, Wei V.
ABSTRACT: Programmed death ligand 1 (PD-L1) plays an essential role in the development or progression of hepatocellular carcinoma (HCC). MicroRNAs (miRNAs) are small RNA molecules that regulate gene expression during normal and pathophysiological events. Here, we explored the functions and detailed mechanisms of miR-378a-3p and PD-L1 in HCC progression. First, miR-378a-3p was selected by analyzing miRNA levels in two HCC Gene Expression Omnibus datasets. We found that miR-378a-3p levels exhibited a downward trend in HCC and were negatively correlated with PD-L1 levels. Additionally, a dual luciferase assay predicted that miR-378a-3p directly targets PD-L1 . Moreover, the transfection of miR-378a-3p mimics into Li-7 and HuH-7 cells effectively decreased the PD-L1 mRNA and protein expression levels, and inhibited Treg differentiation in co-culture models by modulating the expression levels of certain cytokines. Furthermore, the overexpression of miR-378a-3p hindered cell proliferation and migration but facilitated apoptosis by repressing STAT3 signaling in HCC cells. In conclusion, miR-378a-3p appears to inhibit HCC tumorigenesis by regulating PD-L1 and STAT3 levels. Thus, miR-378a-3p may be a potential target for HCC therapy. Graphical abstract: uf0001